Magical Thinking: How Important Is It in Explaining Obsessive-Compulsive Symptoms? A Transcultural Exploration of Magical Thinking and OCD in India and Australia - Barkataki, Bristi (Curtin University, 2019)
This PhD is a mixed-method project of four interrelated studies that explores the importance of magical thinking in explaining obsessive-compulsive (OC) symptoms with a transcultural perspective, between India (holistic-thinking culture) and Australia (analytic-thinking culture). Findings position magical thinking as a unique and important construct implicated in the pathogenesis of OC symptoms. It adds a new facet to the existing cognitive dysfunction model of OCD and warrants more attention, for both theoretical and clinical advancement.